2015
DOI: 10.1111/are.12889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibacterial activity and innate immune components in skin mucus of Indian major carp,Cirrhinus mrigala

Abstract: The present work has been undertaken to analyse the antibacterial activity and innate immune components in the skin mucus of Indian major carp, Cirrhinus mrigala. Skin mucus was extracted separately in triple-distilled water (TDW), 3% acetic acid (3% AA) or 0.1% trifluoroacetic acid (1% TFA). All mucus extracts exhibited different spectrum of the antibacterial activity against different groups of pathogenic bacteria. Protein profiling by polyacrylamide gel electrophoresis revealed a series of protein bands in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Accumulation of mucus in the wound gap soon after the infliction of wound is significant in the light of the reports that fish skin mucus is associated to play various important functions (Plaul, Barbeito, & Díaz, ; Shephard, ). Recently, Balasubramanian et al (), Nigam, Kumari, Mittal, and Mittal (), and Kumari, Nigam, Mittal, and Mittal () suggested that skin mucus play an important role in the protection of the fish against microbial invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of mucus in the wound gap soon after the infliction of wound is significant in the light of the reports that fish skin mucus is associated to play various important functions (Plaul, Barbeito, & Díaz, ; Shephard, ). Recently, Balasubramanian et al (), Nigam, Kumari, Mittal, and Mittal (), and Kumari, Nigam, Mittal, and Mittal () suggested that skin mucus play an important role in the protection of the fish against microbial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Balasubramanian et al (2012), Nigam, Kumari, Mittal, and Mittal (2017), and Kumari, Nigam, Mittal, and Mittal (2011) suggested that skin mucus play an important role in the protection of the fish against microbial invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study reported that the acidic solvent yielded acidic soluble components while aqueous soluble components were extracted in the aqueous solvents in the epidermal mucus of fish (Ong et al, 2010 The result also shown that the acetic acid extracts with the lowest protein concentration exhibited the strongest antibacterial strength among the three extracts. The study by Cole and Ganz (2000) stated that the peptides responsible for pathogen defence were readily soluble in the acidic solvents which selectively precipitated and denatured the proteins, thus leaving the cationic peptides in solution, which believed to be responsible for the antibacterial activity of fish epidermal mucus (Nigam, Kumari, Mittal & Mittal, 2017). The key role in host defence in the epidermal mucus of fish against pathogenic bacteria infection is suggested to be the acidic soluble proteins, potentially paradaxin and pleurocidin from the fish mucus (Cole, Weis & Diamond, 1997;Vennila et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…hydrophila and Vibrio harveyi 34 . Histone proteins have been identified in skin/skin mucus of several teleosts such as histone H4 in mrigal ( Cirrhinus mrigala ) 35 and European sea bass ( D . labrax ) 18 , H2B like protein in channel catfish ( Ictalurus punctatus ) 21 , histone like protein in sunshine bass ( Morone saxatilis ) 36 , histone like protein and H2A in rainbow trout ( Onchorynchus mykiss ) 37,38 , histone derived antimicrobial peptides in Atlantic halibut ( Hippoglossus hippoglossus ) 39 and coho salmon ( Onchorynchus kisutch ) 40 , and histone H2B in lumpfish 16 .…”
Section: Discussionmentioning
confidence: 99%